An iDTMC-based Monte Carlo depletion of a 3D SMR with intra-pin flux renormalization - Kim, Inhyung; Kim, Inyup; Kim, Yonghee (Frontiers in Energy Research, 2022)
Improved deterministic truncation of the Monte Carlo (iDTMC) solution method has been applied to neutronic depletion analyses for the variance reduction. In this paper, the theoretical background on the iDTMC method and material depletion calculation is briefly discussed, and the concept of the intra-pin reconstruction scheme is presented to reproduce the detailed power and flux profiles in an arbitrary geometry with the pin-wise homogenized iDTMC solutions. The iDTMC method is applied and evaluated in a small modular reactor (SMR) problem. Burnup-dependent multiplication factors and pin power distributions are estimated by the iDTMC method with the comparison of the reference and standard MC solutions. Numerical performance has been investigated by the comparison of the real standard deviation, errors, and the computing time. The numerical analysis demonstrate that the iDTMC method is superior to the stadnadrd MC method in estimating the reactor solutions in comparison with the reference solution.